MENINGKATKAN KETERAMPILAN SOSIAL EMOSIONAL ANAK USIA DINI DENGAN BERBANTUAN MEDIA BUKU CERITA BERGAMBAR - Dewi Cahyaningrat (Jurnal Anak Bangsa, 2024)
The aim of the research is to improve children's socio-emotional skills by using the storytelling method. The research was conducted at PAUD Kutilang Petir Serang Group A with 12 students and was carried out in the first semester of the 2023/2024 academic year. The social emotional skills of children aged 4-5 years are still very lacking. The child still likes to play alone, does not want to communicate with his friends, still likes to use his hands and feet with his friends, and the child's ego is still very clear. Research tools include observation sheets and field notes. Collection techniques include observation and documentation. The data obtained was then analyzed descriptively and qualitatively in each cycle. The research results show that children's social emotional improvement occurs in each cycle. The initial condition was only 8.33% which was in the good category. In cycle I, small picture books were used and 50% of the results were in the good category. Children still look dissatisfied and bored using small picture books because they cannot see the pictures clearly, so correction needs to be done in Cycle II. In cycle II the researcher used a ledger. The results achieved were 83.33% which was in the good category. When stories are told with the help of big books, children are very interested in watching them. Children aged 4-5 years begin to concentrate on listening to scientists' stories with the help of a big book, because the pictures in the big book are easy for children to see. Based on this description, it can be concluded that using the big book storytelling method can improve the social emotions of children aged 4-5 years at PAUD Kutilang Petir Serang